Examining the relationship of customer equity drivers (CEDs) on behavioural intentions of spectators from Singapore's professional football clubs - Cheong, Yue Seng (2019)
Background: The decline of spectatorship in the Singapore Premier League (SPL) for the past decade is a concern. Nowadays, sports organisations face strong competition for attention and interest. According to the consumer-equity theory, consumer loyalty-intentions can be effectively attained by designing strategic marketing investments that directly strengthen clubs’ customer equity drivers (CED). With little research incorporating relationship equity and simultaneously studying the impact of CEDs, this study examines the relationship and impact of CED on behavioural intentions of spectators who have watched SPL matches during the 2018 season.